Klausa Eksonerasi dalam Pandangan Hukum Positif dan Maqashid Syariah - Waliyullah, Wong Agung (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Law is a very difficult thing to do considering how the concept of human behavior is very diverse. So that through this, the presence of various legal determinations must also consider various things. One of the things considered regarding legal termination is exoneration. This exoneration is an exception in the legal liability related to several clauses. One of the existing clauses is a parking ticket. Where in some circumstances, the giver of a parking ticket is an exception of liability. What is mentioned in this exoneration seems to contain what is in positive law and maqashid sharia. So in this case the author is interested in conducting research related to the exoneration clause in the view of positive law and maqashid sharia. The research was conducted with the help of the library study method and descriptive analysis. The result is found that exoneration corresponds to both.